Corpos e espaço de performance: abordagens estético-filosóficas para as relações entre corpos humanos e não-humanos em videoperformance - Luciano Soares Mariz (2020)
This research presents aesthetic-philosophical explorations through an inventory of experiences and impressions about the possible relationships between human and non-human bodies, their modes of development in the performance space, during the process of performing in videoperformance. As a methodological strategy, two explorations are described: “Relações Intercorporais” (2018) and “Caixa preta” (2019) as a field of experimentation. These are interpolated from a theoretical overview based on the existence of a relational autonomy of bodies, where the directions do not happen only in a unilateral sense but through stimuli, feedback and creative impulses open to the multiplicities. By the way, the research presents a reflexion about agencies existing in the relations of play between the performer's body and the technical body (in this case, the camera), between these relations, a treatise is proposed that projects a break in the structure of the bodies and conditions the agents to an exploration of their potentialities. The potentials arise through processes of self-organization, where infinite possibilities of deterritorialization and reterritorialization happens with the bodies in the performance action. Through these processes of reterritorialization of bodies and a possibility of approaching them in performance situations, it finds the perspective of a method for creating a Body without Organs (BwO), punctuated by Artaud and developed by Deleuze and Guatarri, in the views of the provocation of a performance space where the bodies find places of suspension and present a body in action, free from the dictatorship of obviousness and materiality.